Employer branding practices impact on employee brand loyalty in private higher education institutions in Pakistan: the mediating role of employee engagement - Ilyas, Muhammad Awais (2019)
Services sector is facing the tremendous challenge in developing a strong employee brand loyalty. Brand loyal employees have intension to stay with organization and committed to deliver high level of services which leads towards consumer satisfaction. Among all the best practices, the most relevant practice known as employer branding which seems relevant in maintaining long term relationship between employee and employer. Although the emergent popularity of the impact of employer branding on employee's behaviour, little is known on how employer branding practices affects existing employee's loyalty behaviour towards their organization's brand. Previous literature on employer branding practices was restricted to potential employees; there is dearth of studies which explore the influence of employer branding practices on existing employee's behaviour. Therefore, the current study attempts to link the relationship between employer branding practices (namely training and development, employer brand reputation, work life balance, organization culture, diversity, corporate social responsibility and compensations and benefits) and employee brand loyalty behaviour. The present study also attempts to examine the mediation role of employee engagement on the initial relationship. Based on psychological contract theory, the offerings (economic, psychological and functional) by the employer brand, influenced the employee's attitude (engagement) and behaviour (loyalty). The proportionate stratified sampling technique was applied. A total of 492 questionnaires were distributed in eighteen private higher educational institutions located in the Punjab province of Pakistan. The 286 questionnaires were useable for further analysis using the PLS-SEM. The results revealed that employer brand reputation, work life balance, organization culture and compensations and benefits have direct significant positive effect and diversity has indirect significant positive effect on employee brand loyalty. The employee engagement mediates the relationships of employer brand reputation, organizational culture and diversity and employee brand loyalty. Finally, this study suggests various recommendations for future research.